KyivGeodynamics++: software for processing satellite laser ranging data - Choliy, V.Ya.; Zhaborovskyy, V.P. (Advances in Astronomy and Space Physics, 2011)
We present the software package KyivGeodynamics++ intended for processing satellite laser ranging data. Review of architecture, the main algorithms, results of the first tests are presented.